Effectiveness of an educational intervention to promote psychosocial well-being of school-going adolescents in Sri Lanka - Chiranthika Vithana; Ayesha Lokubalasooriya; Ganeshamoorthy Pragasan; Kanchana Lanka Mahagamage; Kumudumalee Nanayakkara; Himali Prasangika Herath; Priyani Karunarathna; Nadeeka Perera; Chithramalee de Silva; Dushyanthi Jayawardene; Nuwan Darshana Wickramasinghe (BMC, 2023)
Abstract Background One-fifth of the Sri Lankan population consists of adolescents, with 71% of them schooling. An extreme need exists in the country for the introduction of evidence-based interventions for the psychosocial well-being of adolescents. The present study assessed the effectiveness of an educational intervention to promote the psychosocial well-being of school-going adolescents in grade nine in Western Province, Sri Lanka. Materials and methods A quasi-experimental study was conducted among grade nine students in Western Province in 2019. Panadura Medical Officer of Health (MOH) area was selected as the interventional area (IA), and Kelaniya MOH area was identified as the control area (CA). Teachers at schools in the IA received training on psychosocial health promotion of adolescents. They delivered the activity-based educational intervention package to the grade nine students as 20-min classroom sessions for three months. Pre- and post-intervention assessments of attitudes and practices related to the psychosocial well-being of adolescents were conducted using an interviewer-administered questionnaire. Categorical data were compared using Chi-Square or Fisher's exact test. Mann-Whitney U test was applied to determine the difference between the medians of the pre-and post-intervention scores on attitude and practices for psychosocial well-being. Results A total of 1040 grade nine students were enrolled. There was a statistically significant increase in median score on attitudes [81.8 (IQR:75.5-85.5) to 82.3(IQR:78.6-87.2] and practices [81.7(IQR: 76.1-85.7) to 83.1(IQR: 79.1-86.9)] in the IA while there was no significant difference in the CA. The proportion of bullied adolescents in the past 30 days reduced significantly from 14.8% (n = 38) to 7.9% (n = 20) in IA(p = .03), whereas there was a slight reduction from 17.1% (n = 44) to 11.3% (n = 26) in CA (p = .17). Conclusions The present psychosocial intervention is effective in improving the psychosocial well-being of school adolescents, though long-term effectiveness was not assessed. It is recommended to utilise study findings in deciding to introduce the present intervention to basic and in-service teacher training packages and school curricula with necessary modifications.